Cursos de férias na Escolinha de Arte do Recife: foco na formação de arte/educadores/as de 2016 – 2020 - Carvalho, Auvaneide Ferreira de (2023)
This study sought to investigate how the formative training practices of Art/Educators takes place in the Vacation Courses at Escolinha de Arte do Recife (Little School of Arts of Recife – EAR), from 2016 to 2020. To do so, it was necessary, at first, to identify what are the formative training practices developed there. After that, identify what are the Art Teaching actions carried out at the Escolinha de Arte do Recife, as well as map and analyze which concepts are present in the formative practices developed for the Art/Educators in the EAR Vacation courses, from 2016 to 2020. One can perceive, based on the analysis of studies that are in the Brazilian Digital Library of Theses and Dissertations (BDTD), that there is an invisibility when it comes to art/educators formative training in the EAR. The following dissertation is organized in three sections: the first one deals with the “Escolinhas de Arte” movement as well as it introduces the EAR and its collections, in the light of SILVA; SANTOS; AZEVEDO (2013) and ALVES (2018). The second part of the study deals with the conceptions of formative training practices for Art/Educators, according to ARAÚJO E SILVA (2009), SILVA (2005; 2015) and SILVA (2021). Lastly, the third part talks about non-formal education, in the light of TRILLA (2008) and GOHN (2010). This study is part of a qualitative research approach in Education, and I adopted, during the analysis, the documentary research method (MINAYO, 2016; SÁ-SILVA, ALMEIDA, GUINDANI, 2019). This work highlights the formative training practice for art/educators in the critical-reflective bias of teacher training.